الاستراتیجیة السوریة تجاه العراق بعد عام ٢٠٠٣ (Journal of the College of Education for Women, 2019)
The subject of this thesis acquired it's importance from many sides mostimportant of it , it's the nature of the relationship between Iraq-Syria relationitself . which is basic on many close and fare relationship between them uponthe history , and also the changes that happened in global and regional areaafter the 11th September 2001 and the changes of the American strategy uponSyria , and the trying of the united states to qualify the Syrian role inside itsregional in the meddle east upon the changes that imposing by the unitedstates which is the most important event was the occupation of Iraq .The importance of this subject is also due to the occupation of the unitedstates upon the Iraq on April 2003 which was made the dramatic changes inSyrian strategy specially with Iraq and with using the interference in Iraqiaffairs as a type force the united states and its project inside Iraq .At last, this thesis acquired further importance as it involves study which isvery few in dealing with the Syrian strategy upon Iraq after 2003, and itsfurther, and the importance of the study came also because of thedifficulties in the Syrian situations which is complicated, difficult and changedeven at the same time and same situation.The Problem of thesis :The problem of this thesis start from the idea contains that the Syrianstrategy upon Iraq had dramatic changes after the United States occupiedIraq on 2003 which imaged by the Syrian interference in Iraqi affairs as a toolto face the strategy of the united states in the middle east, and this behaviors of Syria came as the main corals between Syria and Iraq from sideand between the Syria and United States from the other.Hypothesis of the research:This thesis proceeds from a hypothesis to the effect that the changes ofthe American plays which emerged in this thesis by its occupied in Iraq after2003 which had its negative effect in Syrian changes its treatment with Iraqafter 2003, and Syria found that its interference in Iraq is the best paper andchoice to force the United States project inside Iraq and the area. and toprove the troth and the correct of this hypothesis, the matter entails raisingthe following questions :1- what is the influence of American occupied on Iraq upon the Syrianstrategy?2- What is the American vision of the Syrian role in Iraq?3- What is the nature of the relationship between the Iraq-Syria after2003?4- What is the influence of the relationship between the united states –Iraq on the Syrian strategy?5- What is the future of the Syrian strategy upon Iraq?Structure of the thesis :The subject of this thesis necessitated divided it into an introduction, fivesections and a conclusion.The first section is entitled: The Syrian Strategy and its treatment with theoccupation of Iraq.The second section entitled: The American vision for the Syrian role in Iraq.The third section is entitled: The relationship between the Iraq-United statesand its influence upon the Syrian strategy on Iraq.The fourth section is entitled: The dramatic changes in Iraq-Syrianrelationship (the input of changes).The fifth section is entitled: The future of Syrian strategy upon Iraq.